The women's movement and women's employment in nineteenth century Britain - Jordan, Ellen, 1938- (Routledge research in gender and history., 1999)
Ellen Jordan's treatment of the expansion of middle-class women's work is perhaps the most comprehensive available and is a valuable complement to existing works on the social and economic history of women.